Organometallic chemistry of graphene: Photochemical complexation of graphene with group 6 transition metals. (April 2018) - Chen, Mingguang; Pekker, Aron; Li, Wangxiang; Itkis, Mikhail E.; Haddon, Robert C.; Bekyarova, Elena
Abstract: We report the experimental realization of η 6 -complexes of group 6 transition metals with a single layer graphene using photo-activated reactions with organometallic compounds. The reaction progress was followed by in-situ measurements of the graphene conductivity. We observed that the chromium reagents exert the strongest effect on the electronic properties of graphene, leading to (η 6 -graphene)CrL [L = C6 H6, (CO)3 ] complexes with enhanced conductivity. Thus, in the case of covalent functionalization of graphene with Cr(CO)6, the conductivity increased by a factor of 4, while the (η 6 - C6 H6 )Cr(CO)3 reagent doubled the conductivity producing the least enhancement. This mode of covalent bonding preserves the conjugation and the planarity of the graphene structure and offers a promising route for the preparation of a new class of graphitic materials functionalized with transition metals, which may find applications in optoelectronics, spintronics and magnetic nanodevices. Graphical abstract: Image 1